Pendampingan Keluarga Sadar Gizi Seimbang di Desa Dwi Karya Bhakti, Kecamatan Pelepat, Kabupaten Bungo - Silvia Mawarti Perdana; Asparian Asparian; Nurdini Lia (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2021)
Indonesia is still facing the Covid-19 pandemic, as well as Jambi Province. Dwi Karya Bhakti Village is one of the villages located in Pelepat District, Bungo Regency, Jambi Province and become community health target area of UPT Puskesmas (community health centre) Rantau Keloyang. Prevention of Covid-19 can be done by implementing balanced nutrition behavior in the community which consists of four pillars of balanced nutrition, namely: eating variety of foods, clean and healthy lifestyle, physical activity, and monitoring normal body weight (BB). This community service aimed to increase PKK (Family Welfare Empowerment) cadres’s knowledge and skill as part of implementing family balanced nutrition behavior. These projects include: focus group discussions related to community nutrition problems, causes, and solutions by involving puskesmas, PKK cadres, and village governments; and also education and practice of balanced nutrition to 15 PKK cadres. The results of this community service showed that there is difference in the knowledge of PKK cadres in the application of balanced nutrition behavior compared to before participating in mentoring (test score from 84.7 to 93,3). The implementation of balanced nutrition behavior in the family need to be continued as one of the efforts to prevent Covid-19.